Sosialisasi Media Pembelajaran Berbasis Augmented Reality pada Guru Sejarah Sekolah Menengah Atas Kota Jayapura: Socialization of Augmented Reality-Based Learning Media for High School History Teachers in Jayapura City - Handoko, Susanto T.; Kusumo, Handono; Kaban, Theonariya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
21st-century learning requires mastery and utilization of digital technology. Therefore, History Teachers in Jayapura City need to be equipped with mastery of Augmented Reality-based learning media. This community service is very urgently implemented by the History Education Study Program, Faculty of Teacher Training and Education, Cenderawasih University, in collaboration with History teacher partners and developers of AR-based learning media applications. The aims of this community service are: to promote the existence of World War II Cultural Heritage in Jayapura; to promote World War II Cultural Heritage Learning Media using Augmented Reality technology; and to improve the digital literacy of High School history teachers in Jayapura City. The implementation method consists of three stages: the initial, design, and implementation stages. The importance of this community service is that it enhances teachers’ digital literacy, enabling students to engage in innovative, creative, and enjoyable learning.